Hubungan Sosio Demografi dengan Mobilitas Penduduk di Provinsi Jambi (Analisis Data SP-2010) - ., Suandi (PIRAMIDA; Vol 9, No. 2 Desember 2013, 2013)
The purpose of the study are: (1) to describe the socio demographic and population mobility in Jambi Province, and (2) analyze of socio-demographic relationship with population mobility in Jambi Province. The research design is the documentation . The research is focused on Jambi Province. This study takes as long as three months of the calendar. The research data was sourced from the SP-2010 Indonesia. The research variables are: (1) socio - demographic (age of respondent, education level, family size, and employment status ) , and (2) recent migration. The results showed that the average age at recent migration relatively young age group, and there are as many as 33 percent of the population age has not been productive, an elementary education downwards (58%), and worked as laborers (62%). The analysis showed that the recent migration in Jambi Province was negatively related to resource quality and productivity of migrant labor. That is, the increasing number of recent migration then the level of labor productivity was lower.
Keywords: population mobility, labor productivity, quality of human resources, and socio-demographics